Strategie dydaktyki kognitywistycznej: hyper-konstruktywizm i neo-realizm. Podstawy teoretyczne - Karwasz , Grzegorz (Studia Edukacyjne, 2021)
While the term “cognitivistic pedagogy” appeared already in Polish literature, “cognitivistic didactics” is addressed mainly by foreign authors. We define principles and methods of innovative didactics based on constructivistic and cognitivistic theories. The two main paradigms of such didactics consist in constructing the knowledge (and competences) of pupils (listeners, students) in an interactive narration and in using real didactic objects, preferably pulled out of a pocket. We call these concepts hyper-constructivism and neo-realism.